A pharmacist‐managed dosing algorithm for darbepoetin alfa and iron sucrose in hemodialysis patients: A randomized, controlled trial - Francisca Johanna van denOever; Carolien F. M. Heetman‐Meijer; Erwin Birnie; Erwin C. Vasbinder; Eleonora L. Swart; Yvonne C. Schrama (Wiley, 2020)
Abstract The attainment of target hemoglobin levels in hemodialysis patients is low. Several factors play a role, such as hyporesponsiveness to erythropoiesis‐stimulating agents (ESA), but also suboptimal prescribing of ESA and iron. The goal of this study was to investigate if a pharmacist‐managed dosing algorithm for darbepoetin alfa (DA) and iron sucrose improves the attainment of target hemoglobin levels. In this randomized controlled trial, 200 hemodialysis patients from a Dutch teaching hospital were included. In the intervention group (n = 100), a pharmacist monthly provided dose recommendations for DA and iron sucrose based on dosing algorithms. The control group (n = 100) received usual care. In the intervention group, the percentage per patient within the target range (PTR) for hemoglobin (target range 6.8‐7.4 mmol/L) and iron status was higher than in the control group (for hemoglobin median 38.5% vs 23.1%, P = .001 and for iron status median 21.1% vs 8.3%, P = .003). The percentage of high hemoglobin levels (>8.1 mmol/L) was lower in the intervention group (median 0.0% vs 7.7%, P = .034). The weekly dose of DA was lower in the intervention group (median 34.0 vs 46.9 mcg, P = .020), whereas iron dose was higher (median 75 vs 0 mg). No difference was found for the percentage of hemoglobin levels below the target range. In conclusion, a pharmacist‐managed dosing algorithm for DA and iron sucrose increased the attainment of target levels for hemoglobin and iron status, reduced the percentage of high hemoglobin levels, and was associated with a lower DA and a higher iron sucrose dose.